A clinical study on ectopic pregnancy - Soren, Mamata; Patnaik, Ranjita; Sarangi, Bismoy Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Ruptured ectopic pregnancy is a medical emergency; therefore, it is imperative to diagnose the unruptured ectopic pregnancy such that timely intervention will prevent morbidity and mortality Today with availability of monoclonal β-HCG, high resolution transvaginal scan and laparoscopy it is possible to make early diagnosis even before rupture. Methods: Prospective study of two years duration with sample of 72 cases of suspected ectopic pregnancy observed and treated out of total 20193 pregnant women admitted were included in this study. Results: The incidence was 0.36%, maximum between the age group of 26-30 years (33.3%). Risk factors were tubectomy (30.56%), D and C (6.94%), PID (5.6%), previous ectopic (1.39%), IUCD (2.78%). The typical triad of amenorrhoea, pain abdomen and bleeding was observed in 54.2% of cases. 19 patients were brought in shock (26.4%). Ultrasonography done in 56 cases. Conclusions: There is an increase in the incidence of ectopic pregnancy but a decrease in maternal mortality during the past two decades. Although the early diagnostic tools were available, we had to manage most of our patients as surgical emergencies, as they were brought late in the trial, with established diagnosis of ruptured ectopic pregnancy. Physicians should be sensitive to the fact that in the reproductive age group any women presenting with pain in the lower abdomen, diagnosis of ectopic pregnancy should be entertained irrespective of the presence or absence of amenorrhoea, whether or not she has undergone sterilization.